Muslim–Non-Muslim Relations in Conflict and Peace: A Tafsīr Maqāṣidī Reading and its Implications For Plural Citizenship - Zakiyah; Alven Putra; Aan Andesra; Dewi Umus Sarofatul Latifah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2026)
This article examines Muslim–non-Muslim relations through a maqāṣidī reading of Qur‘ān 4:144, 60:1 and 60:8–9, 49:13, and 5:8. Its central concern is the tendency to generalize verses governing loyalty under conditions of threat and conflict into a universal prohibition on relations with non-Muslims within a shared civic order. This library-based study employs Abdul Mustaqim’s thematic-maqāṣidī method. The analysis establishes the textual corpus, examines interverse relations (munāsabah) and historical contexts, analyzes key terms, compares classical, modern, and Indonesian commentaries, constructs an intratextual synthesis, and maps both protective and productive objectives. The findings show that Qur‘ān 4:144 and 60:1 regulate forms of loyalty that may endanger communal security during active hostility; they do not prohibit all social relations with non-Muslims. Qur‘ān 60:8–9 restricts the prohibition to parties engaged in aggression and expulsion, whereas Qur‘ān 49:13 and 5:8 affirm recognition of diversity and justice, including toward groups one may dislike. From a maqāṣidī perspective, this synthesis supports the protection of religious freedom, life, public reason, intergenerational social continuity, equitable economic access, and a constitutional political order. The study thus shifts majority–minority relations from the language of unilateral tolerance toward equal citizenship without eliminating legitimate vigilance against aggression and betrayal.